You tell me what we can do after this: findings and recommendations for the participation of young people with learning disabilities - Charlotte Wilson (Scottish Journal of Residential Child Care)
In recent years the participation of children has been highlighted with ever increasing importance, due to a raft of inquiry reports and legislation. In spite of this, and the increasing number of children defined as 'disabled', the participation of children with learning disabilities has been marginalised and is often described as 'tokenistic'. This article reports on a research project which explored the factors which impact on levels of participation, for children and young people with learning disabilities in a residential short breaks setting.